A Proof-of-Concept Clinical Trial of A Single Luteal Use of Long-Acting Gonadotropin-Releasing Hormone Antagonist Degarelix in Controlled Ovarian Stimulation for In Vitro Fertilization: Long Antagonist Protocol - Papanikolaou, Evangelos G.; Yarali, Hakan; Timotheou, Evi; Grynberg, Michael; Zafeiratis, Odysseas; Tournaye, Herman; Najdecki, Robert (Frontiers in Endocrinology, 2018)
Introduction: A drawback with GnRH antagonist protocols in IVF is they have limited flexibility in cycle programming. This proof of concept study explored the efficacy of a single dose, long-acting GnRH antagonist IVF protocol. Trial registration number: NCT03240159, retrospectively registered, 08-03-2017. Materials & Methods: The efficacy of a single dose long-acting antagonist, Degarelix, was explored initially in healthy donors first and subsequently in infertile patients. In the first part, 5 healthy oocyte donors underwent ovarian stimulation with this new protocol: in the late luteal phase, at Day 24, a bolus injection of degarelix was administered subcutaneously to control the LH surge in the follicular phase. Ovarian stimulation with gonadotropins was initiated subsequently from day 7 to day-10. Endpoints were firstly to inhibit the LH surge later in the follicular phase and, secondly, to retrieve mature oocytes for in vitro fertilization. In the second part, 5 infertile women received the same bolus injection of degarelix administered during the luteal phase at Day 24. Different gonadotropin starting days (day-2 through day-8) were tested in order to observe possible differences in ovarian stimulation. In these infertile patients fresh embryo transfers were performed to assess the pregnancy efficacy of this protocol on pregnancy outcomes and to address any possible negative effects on endometrium receptivity. Results: In the first part of the study, all donors were effectively downregulated with a single luteal dose of degarelix 0.5 mL for up to 22 days until the final oocyte maturation triggering day. Mature oocytes were retrieved 36 hours later from all patients and all produced 2-7 blastocysts. In the second part, all five infertile patients achieved sufficient LH downregulation and completed ovarian stimulation without any LH surge. All patients (except one with freeze all strategy) had blastocysts transferred and pregnancy occurred in 3 out of 5 women Conclusion: A single dose of the long-acting antagonist degarelix during the luteal phase appears to be effective in down-regulating hypophysis during ovarian stimulation. This represents a possible new protocol for IVF, which should be further elucidated in RCTs